2014
DOI: 10.7860/jcdr/2014/8234.4543
|View full text |Cite
|
Sign up to set email alerts
|

3D Laparoscopy - Help or Hype: Initial Experience of A Tertiary Health Centre

Abstract: Introduction: To evaluate the advantages of 3D laparoscopy and compare its significance with conventional 2D laparoscopy during various operative procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Regarding the average duration of the surgical intervention, many studies coincide in a reduction of the procedure time using 3D technology when compared to 2D laparoscopy in various types of surgery [14][15][16][17]. In the study by Costa et al in 2021 in colonic surgery [16], the most frequent surgery performed in the world showed a significantly lower anastomotic time (16.9 ± 2.3 min vs. 19.6 ± 2.9 min) in the 3D group compared to the 2D group.…”
Section: Surgical Time Between 3d and 2d Techniquementioning
confidence: 99%
“…Regarding the average duration of the surgical intervention, many studies coincide in a reduction of the procedure time using 3D technology when compared to 2D laparoscopy in various types of surgery [14][15][16][17]. In the study by Costa et al in 2021 in colonic surgery [16], the most frequent surgery performed in the world showed a significantly lower anastomotic time (16.9 ± 2.3 min vs. 19.6 ± 2.9 min) in the 3D group compared to the 2D group.…”
Section: Surgical Time Between 3d and 2d Techniquementioning
confidence: 99%
“…On the other hand, other recent studies have successfully shown improved performances of experienced surgeons when 3D imaging was used. [19][20][21] Thus, we postulate that a more truly 3D training model could accelerate learning and skills acquisition.…”
Section: Introductionmentioning
confidence: 98%